Analysis and Comparison of Energy Efficiency Code Requirements for Buildings: A Morocco–Spain Case Study - Ikram Merini; Angel Molina-García; M. Socorro García-Cascales; Mustapha Mahdaoui; Mohamed Ahachad (Energies, 2020)
The trend in energy consumption, with a particular focus on heating and cooling demand, is an issue that is relevant to the promotion of new energy policies and more efficient energy systems. Moreover, heating and cooling energy demand is expected to rise in the next several decades, mainly due to climate change as well as increasing incomes in developing countries. In this context, the building sector is currently a relevant energy-intensive economic sector in Morocco; it accounts for 33% of the country’s total energy demand (as the sector with the second highest energy demand, after the transport sector), with the residential sector accounting for 25% and the tertiary sector accounting for 8%. Aiming to reduce energy dependence and promote sustainable development, the Moroccan government recently issued a comprehensive plan to increase the share of renewables and improve energy efficiency. This strategy includes novel thermal building regulations promoted by the Moroccan Agency for Energy Efficiency. This paper analyzes the thermal behavior and heating-cooling energy demand of a residential building located in Tangier (Morocco) as a case example, based on the country’s new thermal regulations and considering specific climatological conditions. A comparison with common Moroccan residential buildings as well as with those in nearby countries with similar meteorological conditions but significant differences in terms of energy demand regulation and requirements, such as Spain, is also included. Simulations were carried out using the DesingBuilder and EnergyPlus Software packages. According to the results, the last building thermal regulation requirements in Morocco need to be revised and extended in order to achieve the energy efficiency objectives established by the Moroccan government for 2030.